Biochemical mechanisms of disorders in the body of warm-blooded under the influence of chemical compounds - Щербань, Николай Гаврилович (Eastern-European Journal of Enterprise Technologies, 2012)
The article represents the analysis of long-term comprehensive sanitary toxicological researches in Kharkiv National Medical University for sanitary rate setting of nonionic, cationic and anionic surfactants in reservoirs’ water. According to the systemic approach, the complex pattern of structural-functional disorders in the body of warm-blooded under the long-term influence of detergents was given. The objects of research were the group of ethoxylated alkylphenols on the basis of propylene trimers (Neonol AF 9 - n), the group of sodium salts of carboxymethylated ethoxylate on the basis of relevant izononilphenols (Neonols APS 9 - n CM), nonionic surfactants on the basis of glycols, the group of nitrogen-containing surfactants on the basis of imidazoline, the group of phosphorous-containing surfactants on the basis of alkylethoxyphosphates. The necessity for such researches is determined by the large production volume and wide application in many sectors of national economy.